Durga Mahishasuramardini - Temples of India Project Team (Jio Institute, 2024)
Six-armed female deity holding a trident, sword in her right; shield, munda in her left hand, rest is not clear. The leg is pressing on his hump, pressing the demon down. The decapitated head is shown fallen down. The lion chomps at the bull/demon's hip. It is stylistically similar to the multiple Durga Mahishasuramardini images recovered from the Harshatmata temple.